2023
DOI: 10.22159/ijoe.2023v11i1.45960
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Computer-Based Test (CBT) and Paper and Pencil Test (PPT) on Academic Achievement and Test Anxiety of Secondary School Students’ in Economics

Abstract: Investigated in this study were the effects of Computer Based Test (CBT) and Paper and Pencil Tests (PPT) on Secondary School (SS) students’ academic achievement and test anxiety in Economics. The pretest-posttest non-randomized control group design was used as the research design. The study was done in Asaba, Delta State, Nigeria. All Senior Secondary II (SSII) students who offered Economics comprised the study’s population. 107 SS II students were selected as the sample. Two instruments - Economics Achieveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…This supports the author's conclusion in Olumese (2019) that the CBT was less expensive than printing and sending big amounts. The similar conclusion was reached by Nikou and Economides (2018) and Abanobi (2022), who found that CBT looked to be superior to paper and pencil testing for both the states that run the assessment programs and the students who engage in them. The CBT has the advantages of cost effectiveness, employing fewer resources and more effective delivery and grading.…”
Section: Discussion Of Findingssupporting
confidence: 65%
See 1 more Smart Citation
“…This supports the author's conclusion in Olumese (2019) that the CBT was less expensive than printing and sending big amounts. The similar conclusion was reached by Nikou and Economides (2018) and Abanobi (2022), who found that CBT looked to be superior to paper and pencil testing for both the states that run the assessment programs and the students who engage in them. The CBT has the advantages of cost effectiveness, employing fewer resources and more effective delivery and grading.…”
Section: Discussion Of Findingssupporting
confidence: 65%
“…A timed, summative, high-stakes examination of student performance using digital devices to run a standardized assessment system is referred to as a "computer-based test" in this context. Answers are provided for this test, and scores are typically computed electronically (Fink, Born, Frey, & Spoden, 2018;Born, Fink, Spoden, & Frey, 2019; In this study, the CBT is described as the effective and efficient monitoring of the academic performances of learners/candidates using modern technological facilities and infrastructure towards the realization of a defined goal When compared to traditional paper-pencil testing, using CBT can enhance students' testtaking motivation, self-efficacy, test perception, and test performance (Nardi & Ranieri, 2018;Rolim & Isaias, 2019;Olumese, 2019;Gu, Ling, Liu, Yang, Kardanova & Loyalka, 2020;Jimoh, Bamiro, Akapo, Ibrahim, & Ismaila, 2020;Olaniyan-Shobowale, Bamiro, Salau & Yahya, 2021;Abanobi, 2022;Olufuwon, Bamiro, Akudo, & Anagun). In order to establish a valid and reliable CBT, similar test results should be established for the conventional Paper-Based Testing (PBT) and its Computer-Based mode, according to the International Guidelines on Computer-Based Testing (International Test Commission, 2004).…”
mentioning
confidence: 99%